Multisystem inflammatory syndrome in adults (MIS-A): cardiovascular manifestations and in-hospital outcomes from two tertiary centers - Nazima Zarubekova; Gaukhar Kurmanova; Almira Akparova; Maira Melis; Almagul Kurmanova; Amina Abdrakhmanova; Sholpan Sadykova; Ademi Samadin; Anna Shin; Zhamilya Zhankina (Frontiers in Cardiovascular Medicine, 2026)
Background Multisystem inflammatory syndrome in adults (MIS-A) is a rare, post-infectious hyperinflammatory condition characterized by multiorgan involvement and substantial cardiovascular morbidity. This study aimed to characterize the cardiovascular phenotype and clinical outcomes of adults with MIS-A and to compare findings between ICU and non-ICU patients. Methods We conducted a multicenter retrospective case series of 22 hospitalized patients with a MIS-A phenotype across two university-affiliated clinical bases in Almaty, Kazakhstan (City Hospital No. 1 and City Hospital No. 7). Data were retrospectively abstracted from completed inpatient medical records after discharge or in-hospital death. Demographics, clinical manifestations documented during hospital days 0−3, baseline laboratory markers (first 24 h), treatments, and outcomes were extracted from medical records. Results The median age was 43 years (IQR, 29−63; range 19−86), and 13/22 patients were female (59.1%). Fever (≥38 °C) was documented on 18/22 (81.8%). Mucocutaneous findings included rash in 12/22 (54.5%), enanthema in 10/22 (45.5%), and non-purulent conjunctivitis in 5/22 (22.7%). Echocardiography was available for 17/22 (77.3%); LVEF <50% was observed in 6/17 (35.3%). Gastrointestinal symptoms occurred in 7/22 (31.8%), neurologic manifestations in 8/22 (36.4%), and respiratory manifestations in 16/22 (72.7%). Inflammatory markers were markedly elevated, including C-reactive protein (median 181 mg/L, IQR, 95.4–245.0) and D-dimer (median 6.4 µg/mL FEU, IQR, 4.0–10.0). Leukocytosis occurred in 15/22 (68.2%), thrombocytopenia in 11/22 (50.0%), and lymphopenia in 8/22 (36.4%). Systemic corticosteroids were used on 14/22 (63.6%); ICU admission occurred on 11/22 (50.0%). In-hospital mortality was 5/22 (22.7%). Conclusion Hospitalized patients with a MIS-A phenotype demonstrated severe hyperinflammation with frequent multiorgan involvement and meaningful in-hospital mortality. Early recognition and standardized assessment of organ dysfunction, particularly cardiovascular involvement, are essential.